Impact and obstetric management of pregnant patients infected with SARS-CoV-2 (Research, Society and Development, 2022)
Maternal physiological and immunological changes can occur during pregnancy, pregnant women may be at increased risk of being infected with SARS-CoV-2 and develop more complicated clinical events. The present study aims to describe the impact of covid-19 during pregnancy and summarize the possible symptoms, treatments, and pregnancy outcomes of women infected with Covid-19 during pregnancy. Carried out through the Virtual Health Library (VHL) in the Pubmed and Scielo databases, using the crossings of the descriptors in English “Pregnancy”, “Covid-19”, “Complications”. To evaluate the research problem and its stratification, the PVO strategy was used. The aforementioned strategy allowed the formulation of the following guiding question: What are the impacts and complications caused by covid-19 during pregnancy? From the guiding question, Boolean operators were used to systematize the searches with the following scheme: Pregnancy AND Covid-19 AND complications. Some pregnancy complications have occurred in pregnant women with Covid-19, such as fetal distress, premature rupture of membranes, premature births and stillbirths. Furthermore, these pregnancy complications may be closely related to cytokine storm, lung injury, and placental ischemia/hypoxia caused by SARS-CoV-2 infections. The increased vulnerability of pregnant women as well as the past experience of previous coronavirus outbreaks is of concern for maternal and fetal complications. The rapid outbreak of the disease, combined with uncertainty as a direct result of the lack of solid scientific data, has forced obstetricians to adapt their current practices in a pragmatic way.